IDENTIFICATION OFPOTENTIALCANDIDATES FORFOREST PRODUCTS INFORESTVILLAGE DESA TAMBAK INDRAGIRI HULU REGENCY - Defri Yoza (JURNAL ILMU-ILMU KEHUTANAN, 2017)
Early stage in the nomination of village forest is preparing information related to village forest conditions that will be proposed in this proposal Village Pond forest. This study aims to identify the potential of timber and non-timber for the database in the nomination of the Village Pond Village forest. Besides, this study to determine the role of forests in the life of villagers Tambak.Based on the results of a survey conducted on the potential of forest products in the village of Forest found the following conclusions: In general, forest conditions and the Village Pond Village Bracelet fit in either category. It is seen by many found trees with diameter> 30 cm. The types that dominate the forest Village Pond and bracelet consists of a kind bengku (Ganua motleyana) family Sapotaceae, back baiku (Cratoxylum formosum) of the family Hypericaceae, chelates guava (Syzygium sp) family syzygium (Myrtaceae), type mersawa (Anisoptera costata ) family meranti / Dipterocarpaceae, the type of varnish (Gluta sp) family tree sap clear / membacang (Anacardiaceae), and others. The potential of forest resources that can be used by communities around the forest of village forest Pond and bracelet consists of forest resources are utilized as a tree beehive and crafts materials for the types of rattan, pandan and bambu.Hutan Village Pond contribute to society in terms of ecology related to hydrology function , economically to fulfill daily needs and social culture in which the trees in the forest Village Pond is used as a raw material for manufacturing lines.